Pain hypersensitivity mechanisms at a glance - Vijayan Gangadharan; Rohini Kuner (Disease Models & Mechanisms, 2013)
There are two basic categories of pain: physiological pain, which serves an important protective function, and pathological pain, which can have a major negative impact on quality of life in the context of human disease. Major progress has been made in understanding the molecular mechanisms that drive sensory transduction, amplification and conduction in peripheral pain-sensing neurons, communication of sensory inputs to spinal second-order neurons, and the eventual modulation of sensory signals by spinal and descending circuits. This poster article endeavors to provide an overview of how molecular and cellular mechanisms underlying nociception in a physiological context undergo plasticity in pathophysiological states, leading to pain hypersensitivity and chronic pain.